Measuring The Application of Corporate Social Responsibility of PT. Gorontalo MineralS - Ahmad Ahmad (Estudiante Law Journal, 2022)
Abstract: This study aims to find out how the legal arrangements for the implementation of Corporate Social Responsibility (CSR) in mining activities and to find out how the analysis of CSR Application Analysis to Communities Around Mining. The research method used is normative juridical with a qualitative approach that is used in the hope that the desired data can be obtained by the author of a clear and complete picture. The results of this study indicate that regulations related to CSR have been regulated in several legal regulations. In government regulation number 47 of 2012 concerning social and environmental responsibility of limited liability companies, it has been explained in article 4 paragraph that says that social and environmental responsibility is carried out by the board of directors based on the company's annual work idea after obtaining an agreement from the board of commissioners or the GMS in accordance with the company's basic budget, unless stipulated otherwise in the statutory provisions«. Law No. 22 of 2001 concerning Oil and Gas. If you look at Law number 22 of 2001 regarding oil and gas, it is not explained in writing that regulates the legal rules related to CSR. However, if you read carefully, there is one provision that alludes to the rule of law. Law Number 3 of 2020 concerning Amendments to Law Number 4 of 2009 concerning Mineral and Coal Mining. Scholarship assistance, buses and several other programs are one of several CSR programs that have been implemented by PT Gorontalo Minerals. Judging from the CSR assistance provided to the community, it has been shown that PT Gorontalo Minerals implements CSR programs in accordance with applicable legal provisions, although only a few CSR programs have been provided by PT Gorontalo Minerals to the community.